Prevalence and risk factors associated with the occurrence of Campylobacter sp. in children aged 6–24 months in peri-urban Nairobi, Kenya - Kiarie, Alice; Bebora, L.; Gitao, G.; Ochieng, Linnet; Okumu, Noah; Mutisya, Christine; Wasonga, Joseph; Masudi, Sherril P.; Moodley, Arshnee; Amon-Tanoh, M.A.; Watson, J.; Cumming, O.; et al. (Frontiers Media, 2023)
Introduction: Campylobacter bacteria is a major cause of foodborne-related bacterial gastroenteritis in humans worldwide. It is known to cause diarrhea in young children which has been shown to directly affect their weight and height as a result of malnutrition. Severe cases of diarrhea can also lead to death. Most of the burden is experienced in resource-limited countries in Africa and Southeast Asia where the disease is linked to poor hygiene and sanitation. The objective of this study was to determine the prevalence of Campylobacter in children aged between 6 and 24 months in Nairobi, Kenya and identify potential risk factors associated with their occurrence.